Improving access to health care in a rural regional hospital in South Africa: Why do patients miss their appointments? - Lucy Frost; Louis S. Jenkins; Benjamin Emmink (AOSIS, 2017)
Background: Access to health services is one of the Batho Pele ('people first') values and principles of the South African government since 1997. This necessitated some changes around public service systems, procedures, attitudes and behaviour. The challenges of providing health care to rural geographically spread populations include variations in socio-economic status, transport opportunities, access to appointment information and patient perceptions of costs and benefits of seeking health care. George hospital, situated in a rural area, serves 5000 outpatient visits monthly, with non-attendance rates of up to 40%. Objectives: The aim of this research was to gain a greater understanding of the reasons behind non-attendance of outpatient department clinics to allow locally driven, targeted interventions. Methods: This was a descriptive study. We attempted to phone all patients who missed appointments over a 1-month period (n = 574). Only 20% were contactable with one person declining consent. Twenty-nine percent had no telephone number on hospital systems, 7% had incorrect numbers, 2% had died and 42% did not respond to three attempts. Results: The main reasons for non-attendance included unaware of appointment date (16%), out of area (11%), confusion over date (11%), sick or admitted to hospital (10%), family member sick or died (7%), appointment should have been cancelled by clerical staff (6%) and transport (6%). Only 9% chose to miss their appointment. The other 24% had various reasons. Conclusions: Improved patient awareness of appointments, adjustments in referral systems and enabling appointment cancellation if indicated would directly improve over two-thirds of reasons for non-attendance. Understanding the underlying causes will help appointment planning, reduce wasted costs and have a significant impact on patient care.